ANALISA BIAYA OPERASIONAL KENDARAAN (BOK) ANGKUTAN PEDESAAN JURUSAN TERMINAL LOKARIA-KLOANGPOPOT KABUPATEN SIKKA - Cristian Abimayus Loreng; Yono Putra; Dedi Imanuel Pau (SIARTEK - Jurnal Teknik Sipil dan Arsitektur, 2023)
Public transportation that plays an important role in supporting the mobility of rural residents is rural public transportation. The function of rural public transportation is to serve rural communities in the fields of education, economy and trade. The ideal village transportation tariff cost factor is the cost that is most affordable for use and can still provide large profits for the operator as a service provider and can maintain the continuity of the village transportation business. The aim of the research is to find out how much the vehicle operating costs (BOK) for village public transport on the Kloangpopot-Terminal Lokaria route, find out how much the tariff is based on the vehicle operating costs (BOK) on the Kloangpopot-Terminal Lokaria route and find out the suitability between the rates in the field and the rates based on operational costs. Vehicles and rates set by the government. To determine the Vehicle Operational Costs (BOK) for village transportation on the Kloangppopot-Lokaria Terminal route, using the method from the decree of the Directorate General of Land Transportation of the Republic of Indonesia whose components include direct costs and indirect costs. The results of this research are that the tariff based on BOK (vehicle operating costs) per year is IDR 4,057,063 /passenger/year, the BOK (vehicle operating costs) tariff per day is IDR 15,500 /passenger, and the tariff for students is IDR 10,500/ passenger. Meanwhile, the rates are according to Sikka Regent's Decree Number 1 of 2022 concerning temporary rates for public passenger transportation within the Sikka Regency area. For the Lokaria-Kloangpopot Terminal route, it is set at IDR 13,000,000 / passenger for the public and students at IDR 7,800